2012
DOI: 10.1007/s00264-012-1511-z
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of patients with spinal tuberculosis: seven-year experience of a teaching hospital in Southwest China

Abstract: Purpose The purpose of this study was to investigate the characteristics of patients managed for spinal tuberculosis at the orthopaedics department of a teaching hospital in Chongqing, China, between 2004 and 2010. Methods The study used a retrospective chart review. The epidemiology, clinical features, laboratory test results, imaging study findings, and treatment methods were recorded. Results The annual incidence of spinal tuberculosis was stable throughout the study period. There were 284 patients, 147 wom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
56
4
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(76 citation statements)
references
References 16 publications
12
56
4
4
Order By: Relevance
“…In our study, patients in rural and urban areas had shorter duration of symptoms compared with what was reported by Wang et al (17) on spinal TB. CST is more severe, and it can cause intolerable discomfort or complete paralysis.…”
Section: Symptom Duration Between Urban and Rural Areassupporting
confidence: 42%
See 2 more Smart Citations
“…In our study, patients in rural and urban areas had shorter duration of symptoms compared with what was reported by Wang et al (17) on spinal TB. CST is more severe, and it can cause intolerable discomfort or complete paralysis.…”
Section: Symptom Duration Between Urban and Rural Areassupporting
confidence: 42%
“…The significant difference in symptom duration between the 2 areas indicated that social and economic disparities had posed challenges to the health of people in rural areas in China. As stated in the study by Wang et al (17), people in rural areas have poor knowledge and awareness to TB and lower economic status in society. Neck pain disappeared almost immediately in patients who underwent surgery, but this was not the case the nonsurgery group, so pain control to help patients become more functional in daily activities is indispensable in the nonsurgery group.…”
Section: Symptom Duration Between Urban and Rural Areasmentioning
confidence: 96%
See 1 more Smart Citation
“…The annual incidence of spinal tuberculosis has remained unchanged in the southwest of China, but if not treated adequately, it may cause serious sequelae [6]. At present, there are no detailed reports about the treatment of cervicothoracic tuberculosis.…”
Section: Discussionmentioning
confidence: 98%
“…The main clinical manifestations of spinal tuberculosis include spinal pain, kyphosis, abdominal mass, and spinal nerve compression (Merino et al, 2012;Wang et al, 2012). Currently, there is still a lack of consensus on a single standard mechanism for its pathogenesis.…”
Section: Discussionmentioning
confidence: 99%